PENURUNAN KANDUNGAN LOGAM BERAT PADA AIR LINDI DENGAN MEDIA ZEOLIT MENGGUNAKAN METODE BATCH DAN METODE KONTINYU - Liliya Dewi Susanawati; Bambang Suharto; Kustamar Kustamar (Agroindustrial Technology, University of Trunojoyo Madura, 2011)
Leacheate could be defined as a liquid from the biological decomposition of decomposed waste that caused by external water that flowing in into the pile of waste. Leacheate caused by a prescipitation liquid into the Final Disposal, both from the rain infiltration or from the water content of the waste itself. Leachate is toxic due to impurities in the deposits that may be derived from industrial waste disposal, dust, the result of processing waste, household hazardous waste, or from the normal decomposition that occurs in trash. If the problem doesnt solved then the landfill that fille with leacheate could contamine the environment and more specific it would contamine ground water and surface water. The results of this study showed the levels of chromium (Cr) was at 0.3892 mg / l and the result treatment that have the most decreasing rate of chromium is at 0.1751 mg / l, while the result for Lead (Pb) is at 2.2923 mg / l and the average result treatment with the best decreasing rate is 0.3940 mg / l at the retention time of 3 weeks. Selection of the best treatment is based on qualitative parameters of wastewater, which is allowed according to the waste quality standard set by the government and different residence time in combinatiaon treatment. Selection of the best treatment P1Z2 give the average Cr content of the smallest since the levels of Cr on initial observation and after treatment P and Z has decreased significantly. And also on treatment P2Z2 give the decreasing rate for the smallest Pb. Pb is a levels at the beginning of the observation and treatment after being given P and Z. Both of these treatments can be interpreted that the treatment effect on levels of Cr and Pb.